The association of the preventive dental practices to the oral health status of the elderly in Multinational Village, Paranaque - Mangapot, Jennifer F.
In order to promote good oral health, Preventive Dentistry is geared toward advocating measures to prevent an increase in the incidence of caries, periodontal disease, and tooth loss (Boehmer et al, 1999). But the current trend of Dental Medicine is directed towards preventive measures for the younger population which tends to disregard the oral status of the older generation. This study aimed to determine the preventive dental behaviors of the elderly such as brushing, flossing, use of adjuncts, frequency of seeking dental treatment and frequency of scaling and polishing and to correlate these practices to their oral health status as determined by the number of functioning teeth, number of root caries, DMFT score, periodontal status (based on bleeding on probing and pocket probing depth) and soft tissue examination. This will also help determine the needs of the elderly population. A survey and oral examination was conducted among 60 senior citizens with ages 60-84 who were randomly selected in Multinational Village. These subjects were categorized into two groups: group A being dentate or partially dentate with or without dentures and group B being the completely edentulous with or without dentures. Based on the results, no significant correlation was observed with the mentioned preventive dental practices and oral health status for both groups. Still, it is important that oral hygiene practices be strictly advocated to the elderly population.